Letter (copy) : S.S. "Yorkbrook" - Citrine, Walter, 1887-1983
011-0109-001 WRS/A WMC/WJB/AC/587 International 24th March, 1937, Mr. W. R. Spence, National Union of Seamen, St. George's Hall, Westminster Bridge Road, S.E.1 Dear Mr. Spence, S.S. "YORKBROOK". We are in receipt of your letter of 22nd instant, giving information in respect to the s.s. "Yorkbrook", for which we thank you. Yours faithfully, General Secretary. 292/946/11/109